Sublethal stress by insecticides on the Neotropical brown stink bug Euschistus heros - Santos, Milaine Fernandes dos (2017)
The insecticide use is the mainly method to control pest species in the agriculture, because reduce the populations. However, the frequently insecticide use can potentially stimulate sublethal effects on species non-target. In the last decades the focus of the researches about the insecticide use has been concentrated about the negative impact on natural enemies and pollinators, but is necessary to know the potential effects caused by insecticides on pest species non-target. In this context, we evaluated the stress induced by insecticide in the survival, mating behavior and reproduction associated to demography of the Neotropical brown stink bug Euschistus heros. In the first experiment, we evaluated the stress by imidacloprid in the survival and reproduction of the stink bug. In the second experiment, we evaluated the secondary stress by chlorantraniliprole, spinosad and pyriproxyfen in the survival and reproduction associated to demography of the stink bug. Finally, in the third experiment we tested the effect by chlorantraniliprole, spinosad and pyriproxyfen in the mating behavior and consequently in the demography of the E. heros. Imidacloprid reduced the female survival compared with untreated females, on the other hand, induced higher levels of cell damage, greater ovariole length, larger area of the most developed follicle in their ovaries up to the 6 th day of adulthood and higher reproduction. Chlorantraniliprole caused mild demographic impact on this pest population, while pyriproxyfen and especially spinosad showed strong demographic impacts. Curiously, chlorantraniliprole cause stimulatory effect on the first copulation of the stink bug. Treated females and/or males with chlorantraniliprole showed increase in the net reproductive rate (R0) and intrinsic rate of population growth (r m ). Our results shows that outbreaks of E. heros in the soybean are related to hormesis induced by low concentrations of imidacloprid and also by chlorantraniliprole. In other hand, spinosad and pyriproxyfen decreases the population growth and are potential insecticides for use in control programs of the Neotropical brown stink bug E. heros in Brazil.